2020
DOI: 10.3390/jof6030178
|View full text |Cite
|
Sign up to set email alerts
|

UhAVR1, an HR-Triggering Avirulence Effector of Ustilago hordei, Is Secreted via the ER–Golgi Pathway, Localizes to the Cytosol of Barley Cells during in Planta-Expression, and Contributes to Virulence Early in Infection

Abstract: The basidiomycete Ustilago hordei causes covered smut disease of barley and oats. Virulence effectors promoting infection and supporting pathogen lifestyle have been described for this fungus. Genetically, six avirulence genes are known and one codes for UhAVR1, the only proven avirulence effector identified in smuts to date that triggers complete immunity in barley cultivars carrying resistance gene Ruh1. A prerequisite for resistance breeding is understanding the host targets and molecular function of UhAVR1… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 87 publications
(161 reference statements)
0
6
0
Order By: Relevance
“…The next closest similarity is to Tin1-3 and Tin1-6 of U. maydis which, respectively, are most closely related to Vag2 and Sr10052.2 of S. reilianum [ 67 ]. In contrast to vag2 which was expressed throughout the biotrophic phase with the highest values in young ears ( Figure 3 A), Uhavr1 was expressed only in the early stages of the biotrophic phase [ 68 ] suggesting specific roles of the two proteins in their respective pathosystems. UhAvr1 was shown to lead to complete immunity in barley cultivars carrying the resistance gene Ruh1, which triggers hypersensitive cell death (HR).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The next closest similarity is to Tin1-3 and Tin1-6 of U. maydis which, respectively, are most closely related to Vag2 and Sr10052.2 of S. reilianum [ 67 ]. In contrast to vag2 which was expressed throughout the biotrophic phase with the highest values in young ears ( Figure 3 A), Uhavr1 was expressed only in the early stages of the biotrophic phase [ 68 ] suggesting specific roles of the two proteins in their respective pathosystems. UhAvr1 was shown to lead to complete immunity in barley cultivars carrying the resistance gene Ruh1, which triggers hypersensitive cell death (HR).…”
Section: Discussionmentioning
confidence: 99%
“…UhAvr1 was shown to lead to complete immunity in barley cultivars carrying the resistance gene Ruh1, which triggers hypersensitive cell death (HR). In contrast, in susceptible plants, the protein contributes to fungal virulence by suppressing general defense responses including nonhost/PTI and ETI invoked by various pathogens [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…Montenegro Alonso and coworkers. They found that the effector protein is required for virulence on susceptible barley, induced a hypersensitive reaction (HR) in resistant barley cultivars, was secreted via the ER–Golgi pathway, located to the cytosol when expressed in plant cells, and had a role in suppressing conserved plant basal immunity components [ 9 ]. Effectors of U. maydis were the object of study of J.R.L.…”
Section: Biotrophy—smuts Entering and Living In The Plant Realmmentioning
confidence: 99%
“…However, heterologous expression of some effectors in planta can result in strong pleiotropic defects that compromise symptom evaluations. In another strategy, the type III secretion system (T3SS) of Pseudomonas syringae (for Arabidopsis) and Pseudomonas fluorescens or Pseudomonas atropurpurea (for wheat and barley) is used for functional characterization of several intracellular effectors from obligate biotrophs, such as rusts and powdery mildews [11][12][13][14][15]. Any growth promotion observed for Pseudomonas sp.…”
Section: Introductionmentioning
confidence: 99%
“…Any growth promotion observed for Pseudomonas sp. transformants, which deliver the desired effectors into the host cell during infection, is interpreted as a positive contribution to virulence [11][12][13][14][15]. However, the T3SS of Pseudomonas sp.…”
Section: Introductionmentioning
confidence: 99%